2016
DOI: 10.1038/srep20352
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α is localized to neurofibrillary tangles in Alzheimer’s disease

Abstract: The female predominance for developing Alzheimer disease (AD) suggests the involvement of gender specific factor(s) such as a reduced estrogen-estrogen receptor signaling in the pathogenesis of AD. The potential role of ERα in AD pathogenesis has been explored by several groups with mixed results. We revisited this issue of expression and distribution of ERα in AD brain using a specific ERα antibody. Interestingly, we found that ERα co-localized with neurofibrillary pathology in AD brain and further demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 63 publications
0
32
0
1
Order By: Relevance
“…Therefore, it is most likely that tau expression and/or pathology may affect SREBP‐2 signaling through transcriptional regulation. In this regard, we found that tau expression inhibited the transcription activity of estrogen receptor and its downstream signaling . Indeed, the mRNA levels of the SREBP‐2 target genes including SREBP‐2 and HMGcoAR are reduced in AD (Figure F).…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, it is most likely that tau expression and/or pathology may affect SREBP‐2 signaling through transcriptional regulation. In this regard, we found that tau expression inhibited the transcription activity of estrogen receptor and its downstream signaling . Indeed, the mRNA levels of the SREBP‐2 target genes including SREBP‐2 and HMGcoAR are reduced in AD (Figure F).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, our work could be used not only for future research where turns with an Xaa‐Pro cis conformation are required for modulation of the FKBP52 FK1 domain but also in the understanding of its link with hERα and Tau …”
Section: Discussionmentioning
confidence: 99%
“…E2 has a neuroprotective effect in several animal models of neurodegenerative diseases, such as ischemia, AD and experimental autoimmune encephalomyelitis (EAE; Arevalo et al, 2015 ). In addition, ERα interaction with neurofibrillary tangle and NGB-Aβ complexes suggest that proteins aggregates with ERα and NGB may inhibit their functions, therefore de-regulation impairs neuroprotective effect in AD (Sun et al, 2013 ; Seal et al, 2015 ; Wang et al, 2016 ). NGB is co-expressed with ERα in specific hypothalamic regions (Hundahl et al, 2008 ; Cutrupi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%